Tuntunan Al-Qur’an dan Hadis dalam Pengembangan IPTEK - Nuruddin, Nuruddin; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2025)
The Qur’an and Hadith serve not only as guides for worship but also contain foundational principles that support the development of science and technology (IPTEK). This article aims to examine the Islamic perspective on the importance of knowledge and how the Qur’an and Hadith provide philosophical, ethical, and practical foundations for scientific exploration. Using a descriptive qualitative method through a literature review, the study finds that numerous Qur’anic verses and prophetic traditions encourage intellectual activity, research, and scientific development as forms of scholarly responsibility and worship to Allah. In Islam, science and technology are not merely tools for progress but are also spiritual means to draw closer to Allah and to promote the welfare (maslahah) of humanity. History records the advancement of science and technology within Islamic civilization, producing renowned scholars whose contributions remain influential, affirming Islam’s support for scientific achievement. Moreover, Islamic spiritual values serve as an ethical framework to ensure that technological applications remain aligned with the principles of benefit and morality. Thus, the integration of religious values and science and technology is a vital strategy for building an advanced and ethical Islamic civilization.